Woman as enemy of the nation-state: citizenship, transgression and legacy in Maps and Half of a Yellow Sun - Koeries, Noélle (Department of English Language and Literature, 2018)
This thesis brings to the fore two non-focalising characters, Misra of Maps by Nuruddin Farah and Kainene of Half of a Yellow Sun by Chimamanda Ngozi Adichie. These transgressive characters are placed at the centre of their respective narratives. The aim is to demonstrate the way they transgress conventional political, social, national and gendered boundaries. This transgression creates the space for an alternative citizenship to emerge. The type of citizenship that is multi-faceted and embraces the complexity and nuances of contested borders. These transgressions are read as legacy especially because neither Misra nor Kainene bring to fruition the potentialities and possibilities of their subversive natures. However, both novels present alternatives that reach beyond the closing of the narratives. Ultimately, this thesis questions the purpose of writing transgressive woman characters out of the official narrative.